Pemberian Kompos Ampas Tahu dan Urine Sapi Pada Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis jacq) - Roni Tua; Sampoerno '; Edison Anom (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Palm Oil plant (Elaeis guineensis Jacq) is one of the most important crops which is plays an important role for Indonesia as a mainstay for export commodities and commodities that can increase the income of Indonesian society. Nursery activities essentially instrumental in the preparation of plant material (seeds) for planting in the field, so the breeding activities must be managed properly. Provision of compost fertilizer on the media used in oil palm seedlings is expected to add the availability of macro and micro nutrients in the soil, so it can increase the biological soil microbes and earthworms  better. To have a good quality seeds, there is ne option through regulatory substances growing plants. The use regulatory substances growing plants on nursery synthetic or naturally aims to enhance the growth of seedlings. One of the regulatory substances growing plants is cow’s urine, in addition to relatively easily obtainable also simple to use. Based on these results it can be concluded that the subtances of cow urine and tofu compost generally showed different results is not apparent after a statistical analysis on the parameters except the ratio of canopy and root dry weight of seedlings. Giving cow urine at a concentration of 40% and compost tofu 225 g / plant has not followed the maximum results in all parameters tested.   Keywords: palm seeds,compost, cow urine.